Diagnosis and Treatment of Thoracic Outlet Syndrome: A Systematic Review of Imaging Modalities, Conservative Interventions, and Surgical Approaches - Joanna Wziątek; Piotr Kowalik; Magdalena Strzelczyk; Paula Bętkowska; Iwona Koziołek; Gabriela Pabis; Patrycja Fatyga; Daria Krzyżanowska; Wiktoria Fatyga; Kinga Dowierciał (Quality in Sport)
Thoracic outlet syndrome (TOS) is a rare condition that primarily affects people in the first half of their lives. TOS is divided into three types depending on the affected structures: neurogenic, arterial, and venous. The spectrum of symptoms is broad, ranging from their complete absence to life-threatening thromboembolic events. Due to the lack of clear guidelines, diagnosis is difficult and prolonged. Materials and methods This review includes an analysis of recent clinical trials and studies. It was prepared by analyzing data from PubMed, covering the period from 2008 to 2025. The studies were selected using the keywords: „thoracic outlet syndrome”, „brachial plexus compression”, „neurovascular compression”, „Paget-Schroetter syndrome”, „rib resection” and „diagnostic imaging”, along with time filters. Aim of the study This study aims to review the methods of diagnosis and treatment of thoracic outlet syndrome, focusing on imaging techniques and conservative management. Summary The study shows that difficulties in accurately diagnosing and classifying thoracic outlet syndrome (TOS) still persist. A correlation between clinical symptoms and imaging results is necessary. Both conservative and surgical treatment methods are highly effective in reducing the symptoms of the condition. The approach to diagnosis and treatment should be tailored individually by a highly qualified specialist with experience in this field.